2023
DOI: 10.3390/medicina59030444
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inverted Papilloma Surgical Removal for Sleep Apnea Treatment Success—A Case Report

Abstract: In recent years, increased attention has been directed to sleep apnea syndrome due to its high prevalence and preventable severe health consequences. Besides enhancing the risk of cardiovascular, cerebrovascular, and metabolic disorders, it determines increased daytime somnolence, cognitive impairment, and delayed reaction time. These symptoms, determined by sleep fragmentation and chronic hypoxemia, can result in a decrease in professional performance and, moreover, could have tragic implications, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Although isolated nasal surgery alone has not been shown to correct AHI [27], multiple studies have demonstrated that nasal surgery can improve subjective measures nasal obstruction and improve CPAP use and effectiveness [28,29]. Sinonasal pathologies, such has nasal polyposis and inverted papilloma have been shown to negatively affect OSA and CPAP compliance necessitating adequate disease control in order to improve OSA [30][31][32]33 & ] Surgical correction of nasal obstruction often involves septoplasty, inferior turbinate reduction, and/or internal nasal valve repair. Additionally, in patients with chronic rhinosinusitis, endoscopic sinus surgery can improve mucosal inflammation causing nasal obstruction [34].…”
Section: Key Pointsmentioning
confidence: 99%
“…Although isolated nasal surgery alone has not been shown to correct AHI [27], multiple studies have demonstrated that nasal surgery can improve subjective measures nasal obstruction and improve CPAP use and effectiveness [28,29]. Sinonasal pathologies, such has nasal polyposis and inverted papilloma have been shown to negatively affect OSA and CPAP compliance necessitating adequate disease control in order to improve OSA [30][31][32]33 & ] Surgical correction of nasal obstruction often involves septoplasty, inferior turbinate reduction, and/or internal nasal valve repair. Additionally, in patients with chronic rhinosinusitis, endoscopic sinus surgery can improve mucosal inflammation causing nasal obstruction [34].…”
Section: Key Pointsmentioning
confidence: 99%